Food fortification with multiple micronutrients: impact on health outcomes in general population - Das, Jai K (Cochrane Database Syst Rev, 2019)
BACKGROUND: Vitamins and minerals are essential for growth and maintenance of a healthy body, and have a role in the functioning of almost every organ. Multiple interventions have been designed to improve micronutrient deficiency, and food fortification is one of them. OBJECTIVES: To assess the impact of food fortification with multiple micronutrients on health outcomes in the general population, including men, women and children. SEARCH METHODS: We searched electronic databases up to 29 August 2018, including the Cochrane Central Register of Controlled Trial (CENTRAL), the Cochrane Effective Practice and Organisation of Care (EPOC) Group Specialised Register and Cochrane Public Health Specialised Register; MEDLINE; Embase, and 20 other databases, including clinical trial registries. There were no date or language restrictions. We checked reference lists of included studies and relevant systematic reviews for additional papers to be considered for inclusion. SELECTION CRITERIA: We included randomised controlled trials (RCTs), cluster‐RCTs, quasi‐randomised trials, controlled before‐after (CBA) studies and interrupted time series (ITS) studies that assessed the impact of food fortification with multiple micronutrients (MMNs). Primary outcomes included anaemia, micronutrient deficiencies, anthropometric measures, morbidity, all‐cause mortality and cause‐specific mortality. Secondary outcomes included potential adverse outcomes, serum concentration of specific micronutrients, serum haemoglobin levels and neurodevelopmental and cognitive outcomes. We included food fortification studies from both high‐income and low‐ and middle‐income countries (LMICs). DATA COLLECTION AND ANALYSIS: Two review authors independently screened, extracted and quality‐appraised the data from eligible studies. We carried out statistical analysis using Review Manager 5 software. We used random‐effects meta‐analysis for combining data, as the characteristics of study participants and interventions differed significantly. We set out the main findings of the review in 'Summary of findings' tables, using the GRADE approach. MAIN RESULTS: We identified 127 studies as relevant through title/abstract screening, and included 43 studies (48 papers) with 19,585 participants (17,878 children) in the review. All the included studies except three compared MMN fortification with placebo/no intervention. Two studies compared MMN fortification versus iodised salt and one study compared MMN fortification versus calcium fortification alone. Thirty‐six studies targeted children; 20 studies were conducted in LMICs. Food vehicles used included staple foods, such as rice and flour; dairy products, including milk and yogurt; non‐dairy beverages; biscuits; spreads; and salt. Fourteen of the studies were fully commercially funded, 13 had partial‐commercial funding, 14 had non‐commercial funding and two studies did not specify the source of funding. We rated all the evidence as of low to very low quality due to study limitations, imprecision, high heterogeneity and small sample size. When compared with placebo/no intervention, MMN fortification may reduce anaemia by 32% (risk ratio (RR) 0.68, 95% confidence interval (CI) 0.56 to 0.84; 11 studies, 3746 participants; low‐quality evidence), iron deficiency anaemia by 72% (RR 0.28, 95% CI 0.19 to 0.39; 6 studies, 2189 participants; low‐quality evidence), iron deficiency by 56% (RR 0.44, 95% CI 0.32 to 0.60; 11 studies, 3289 participants; low‐quality evidence); vitamin A deficiency by 58% (RR 0.42, 95% CI 0.28 to 0.62; 6 studies, 1482 participants; low‐quality evidence), vitamin B2 deficiency by 64% (RR 0.36, 95% CI 0.19 to 0.68; 1 study, 296 participants; low‐quality evidence), vitamin B6 deficiency by 91% (RR 0.09, 95% CI 0.02 to 0.38; 2 studies, 301 participants; low‐quality evidence), vitamin B12 deficiency by 58% (RR 0.42, 95% CI 0.25 to 0.71; 3 studies, 728 participants; low‐quality evidence), weight‐for‐age z‐scores (WAZ) (mean difference (MD) 0.1, 95% CI 0.02 to 0.17; 8 studies, 2889 participants; low‐quality evidence) and weight‐for‐height/length z‐score (WHZ/WLZ) (MD 0.1, 95% CI 0.02 to 0.18; 6 studies, 1758 participants; low‐quality evidence). We are uncertain about the effect of MMN fortification on zinc deficiency (RR 0.84, 95% CI 0.65 to 1.08; 5 studies, 1490 participants; low‐quality evidence) and height/length‐for‐age z‐score (HAZ/LAZ) (MD 0.09, 95% CI 0.01 to 0.18; 8 studies, 2889 participants; low‐quality evidence). Most of the studies in this comparison were conducted in children. Subgroup analyses of funding sources (commercial versus non‐commercial) and duration of intervention did not demonstrate any difference in effects, although this was a relatively small number of studies and the possible association between commercial funding and increased effect estimates has been demonstrated in the wider health literature. We could not conduct subgroup analysis by food vehicle and funding; since there were too few studies in each subgroup to draw any meaningful conclusions. When we compared MMNs versus iodised salt, we are uncertain about the effect of MMN fortification on anaemia (R 0.86, 95% CI 0.37 to 2.01; 1 study, 88 participants; very low‐quality evidence), iron deficiency anaemia (RR 0.40, 95% CI 0.09 to 1.83; 2 studies, 245 participants; very low‐quality evidence), iron deficiency (RR 0.98, 95% CI 0.82 to 1.17; 1 study, 88 participants; very low‐quality evidence) and vitamin A deficiency (RR 0.19, 95% CI 0.07 to 0.55; 2 studies, 363 participants; very low‐quality evidence). Both of the studies were conducted in children. Only one study conducted in children compared MMN fortification versus calcium fortification. None of the primary outcomes were reported in the study. None of the included studies reported on morbidity, adverse events, all‐cause or cause‐specific mortality. AUTHORS' CONCLUSIONS: The evidence from this review suggests that MMN fortification when compared to placebo/no intervention may reduce anaemia, iron deficiency anaemia and micronutrient deficiencies (iron, vitamin A, vitamin B2 and vitamin B6). We are uncertain of the effect of MMN fortification on anthropometric measures (HAZ/LAZ, WAZ and WHZ/WLZ). There are no data to suggest possible adverse effects of MMN fortification, and we could not draw reliable conclusions from various subgroup analyses due to a limited number of studies in each subgroup. We remain cautious about the level of commercial funding in this field, and the possibility that this may be associated with higher effect estimates, although subgroup analysis in this review did not demonstrate any impact of commercial funding. These findings are subject to study limitations, imprecision, high heterogeneity and small sample sizes, and we rated most of the evidence low to very low quality. and hence no concrete conclusions could be drawn from the findings of this review.